Green, Closed Loop, and Reverse Supply Chain: A literature review - Roya Anvari (Training & Research Institute - Jeramba Ilmu Sukses, 2023)
This paper is the first attempt in reviewing and categorizing the literature in three different fields of supply chain including: Green Supply Chain (GSC), Closed Loop Supply Chain (CLSC) and Reverse Supply Chain (RSC) those are partially interconnected. For this reason, each one of these three topics has been divided into several criteria and each criterion is a review of several similar issues. This research aims to: Clarify the different area undergone the researcher’s investigation in the three mentioned filed of supply chain management; Show the differences and similarities of green supply chain management, closed loop, supply chain management and Reverse supply chain management; Provide researchers with future research directions in these three fields. This research tries to reach the mentioned objectives through reviewing the other research and summarizing them in parts. The first part will discuss what has been done and second part is reviewing what have been found. Finding also discusses what is done regarding these three topics and their boundaries as well as recommendations for future works (What can be done).